A Cross‐cultural comparison of saturation, vividness, blackness and whiteness scales. Issue 2 (13th June 2016) - Cho, Yoon Ji; Ou, Li‐Chen; Luo, Ronnier
Abstract: In a typical Euclidean three‐dimensional colour space such as CIELAB, the 'third‐dimension', such as CIELAB chroma, has long been criticized as being confusing and difficult to understand for naïve observers and it had relatively poor consistency in visual assessments. As an attempt to find a promising replacement to existing 'third‐dimension', two psychophysical experiments were conducted in this study using naïve observers. In the first experiment, 24 Korean observers assessed 48 NCS colour chips in terms of bright, light‐heavy, active‐passive, fresh‐stale, clean‐dirty, clear, boring, natural‐not natural, warm‐cool, intense‐weak, saturated, vivid‐dull, distinct‐indistinct, full‐thin and striking. According to experimental results, 'saturated' and 'vivid‐dull' were found to highly correlate with CIELAB chroma and were thus regarded as good candidates to become alternatives to existing 'third‐dimension'. In the second experiment, 40 Korean and 68 British observers assessed more than 100 samples in terms of saturation, vividness, blackness and whiteness. Thus, observers assessed 120 samples for saturation, vividness and whiteness. For blackness, 110 samples were assessed. In both experiments, the colour samples were presented in a viewing cabinet and assessed individually. Principal component analysis identified two components that were associated with CIELAB lightness and chroma. In general, there was a similarity between the visual results of the British and Korean observers. High correlation coefficients were found for the following comparisons: predicted values of Berns' depth model versus the present 'saturation' response; Berns' clarity versus 'vividness' response; Berns' vividness versus 'blackness' response; and CIELAB lightness versus 'whiteness' response. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 203–215, 2017